How escapism leads to behavioral intention in a virtual reality store with background music? - Loureiro, S. M. C.; Guerreiro, J.; Japutra, A. (Journal of Business Research, 2021)
Despite the technological advances, empirical studies to understand how VR influences consumer behavior have been limited to date. This study aims (i) to extend the S(Stimuli)-O (Organism)-R (Response) framework by considering escapism as stimuli and incorporating vividness and telepresence as an organism and (ii) examine the role of calm versus upbeat music tempo in the background. Based on an experimental study of between-groups factorial design with two hundred participants, the results offer support to our conceptual framework. Escapism, which functions as experience, stimulates the consumers’ cognitive and affective state that increase pleasure. Subsequently, the consumers’ sense of pleasure heightens the vividness and presence of the virtual reality store, which positively affects their intentions. The link between presence and behavioral intention is stronger with calm music in the background. On the contrary, the link between arousal and pleasure is stronger when consumers listen to upbeat music in the virtual store.